Emotional Education in Vulnerable Contexts. An Emotion- and Art-Based Intervention in a Primary School - Paula Sarria-Martínez; María del Valle Moya-Martínez; Alonso Mateo-Gómez (Revista Electrónica Educare)
Objective. This study aimed to verify the effectiveness of an intervention based on Emotional Intelligence (EI) and the arts. Method. A didactic program was conducted to develop EI with 55 Primary Education students, ranging from 8 to 12 years old. The program focused on artistic and musical activities. The participants belonged to a school with high rates of marginality and social exclusion. The data were collected through a pretest, a post-test, and a deferred post-test, with the TMMS24-Questionnaire, to assess EI in three dimensions: attention, clarity, and emotional repair. Results. After data collection, the study analyzed the students’ performance in the emotional dimensions; it found significant improvements in most of the dimensions studied. Conclusions. The main results show the usefulness of these programs in improving the EI of students in disadvantaged environments.